Etica ed estetica: somaestetica e l'arte di vivere (Lebenswelt. Aesthetics and philosophy of experience., 2013)
Ethics and aesthetics tend to be sharply distinguished and frequently opposed as rival realms of value. The apparent conflict between them is discomforting for artists and theorists who seek to combine aesthetic values and ethical aims in their work. My article strives to ease this theoretical tension in two ways. First, through a genealogical analysis of the complexity of our concepts of ethics and aesthetics, I argue that, in some of their historical conceptions, they display considerable convergence. Here I appeal both to classical Western and Asian theories of ethics and aesthetics. Second, I show how these notions converge in the pragmatist, somaesthetic notion of an embodied art of living.